Influence of slow and rapid weight loss periods on physiological performance, mood state and sleep quality in male freestyle wrestlers: a study from Sichuan Province, China - Yu, Liang; Lei, Lan; Cheng, Liang (Frontiers in Psychology, 2024)
Objective This study aims to investigate the changes in physiological performance, mental state and sleep quality during the weight reduction phase prior to competition in male freestyle wrestlers. Methods This study included 16 male freestyle wrestlers from Sichuan Province, China. Participants were evaluated at three time points: the first day of slow weight reduction (T1, March 26), the first day of rapid weight reduction (T2, April 26) and the day before the competition (T3, May 3), and measurements were taken for physiological performance, mood state and sleep quality. Results The most relevant findings indicated the following: Morning heart rate, creatine kinase and fatigue scores increased by 12.6, 64.6, and 19.0%, respectively, from T1 to T2 (p < 0.05), and decreased by 14.1, 36.6, and 16.8%, respectively, from T2 to T3 (p < 0.05). Hemoglobin and testosterone levels decreased by 3.0 and 16.8%, respectively, from T1 to T3 (p < 0.05), and by 2.9 and 18.2%, respectively, from T2 to T3 (p < 0.05); The secondary findings revealed the following: The total mood disturbance scores decreased by 3.8% from T2 to T3 (p = 0.072), positive mood scores decreased by 9.0% from T1 to T2 (p = 0.090), the Pittsburgh Sleep Quality Index total scores increased by 14.4% from T1 to T2 (p = 0.323) and total work output and average power output decreased by 7.3 and 7.8%, respectively, from T1 to T3 (p = 0.067, p = 0.052); Regression analyses predicted negative mood (Y1 = 62.306–0.018 × maximum power output) and sleep quality (Y2 = 2.527 + 0.278 × Immunoglobulin G) during the weight reduction period. Conclusion The combined slow and rapid weight reduction approach effectively minimized body fat in athletes with limited effect on their physiological performance and sleep quality. However, the effects were adverse on certain health variables and anaerobic power in Chinese male freestyle wrestlers. The identified correlations between negative mood and maximum power, and between sleep quality and immunoglobulin G, shed new light on factors influencing athletes’ well-being during weight reduction, and underscored the need for careful monitoring of physiological variables in future weight management strategies.